Obligatory Prayer Practice Based on Mobile Learning - Hakim, Abdul; Purbohadi, Dwijoko; Setiawan, Asep (Emerging Information Science and Technology, 2022)
Commencing with dawn, zuhr, asr, maghrib, and concluding with isha, obligatory prayers are conducted five times a day. These are the first worship that will be weighed on the last day. Printed materials are frequently utilized to teach the practice of praying. It is feasible, however, to produce a monotonous quantity of learning. Today, technology development and information have influenced an individual’s learning style and behavior. In order to provide an exciting and engaging learning environment, this study designed a mobile learning application for obligatory prayer practice. This study employed an experimental method to develop the application and questionnaires to collect the data. The application could display readings of prayers, images of the prayer movement, videos of the prayer movement, and audio readings of prayers, as well as some of the most influential summaries, positions, and laws for leaving a prayer.